Verbascoside-Rich Plant Extracts in Animal Nutrition - Raffaella Rossi; Edda Mainardi; Francesco Vizzarri; Carlo Corino (MDPI AG, 2023)
In recent years, the search for dietary intervention with natural products able to sustain animal health and decrease environmental impact, has raised the number of studies pertaining to the use of plants' secondary metabolites. In fact, in livestock, there is a clear relationship between the animals' antioxidant status and the onset of some diseases that negatively affect animal welfare, health, and productive performance. An interesting compound that belongs to the secondary metabolites family of plants, named phenylpropanoids, is verbascoside. The genus Verbascum, which includes more than 233 plant species, is the genus in which this compound was first identified, but it has also been found in other plant extracts. Verbascoside exhibits several properties such as antioxidant, anti-inflammatory, chemopreventive, and neuroprotective properties, that have been evaluated mainly in in vitro studies for human health. The present work reviews the literature on the dietary integration of plant extracts containing verbascoside in livestock. The effects of dietary plant extracts containing verbascoside on the productive performance, antioxidant status, blood parameters, and meat quality in several animal species were evaluated. The present data point out that dietary plant extracts containing verbascoside appear to be a favorable dietary intervention to enhance health, antioxidant status, and product quality in livestock.